Perceived benefits and burdens encountered by relatives caring for persons on long-term haemodialysis in Johannesburg - Kuture, Shingai Mushandimai (My University, 2014)
Perceived benefits and burdens encountered by relatives caring for person on long-term haemodialysis in Johannesburg. This study examines the perceived benefits and burdens of family members caring for persons on long term Haemodialysis. The caregiver burden scale by Elmastahl, Malmeberg and Annerstedtl (1996) was used for the purposes of the study. The participants were selected by Census (total) sampling. The sample consisted of family caregivers who were 18 years and above who were selected from three haemodialysis units in Johannesburg. Permission to conduct the study was requested and granted from all relevant authorities. One hundred and fifty questionnaires were distributed amongst the three haemodialysis units of which seventy nine participants responded to the study. Data were analysed using the statistical package STATA version 12. Demographic data and the caregiver burden scale were analysed through frequency counts, percentages and graphs were constructed from the collected data and analysed. Cross tabulations, using Fisher’s exact test were performed to determine the relationship between the demographic information and factors of the caregiver burden scale. The results are presented in the form of tables and graphs. Semi structured questionnaire with an option for elaboration were analysed using content analysis to enumerate a deeper understanding of the perceived burdens and benefits of caring for a person on Haemodialysis. Findings from the study concluded that family caregivers have encountered both benefits and burdens when caring for a person on Haemodialysis. The following factors have emerged namely demographics which include age, gender, relation to patient, highest education level, employment, ethnicity and duration of care and the factors surrounding general strain, isolation, disappointment, emotional involvement and environment. The factors, whether good or poor, are not always a predictor of perceived benefits and burdens of caring for persons on long term haemodialysis. The overall caregiver burden score, inclusive of all factors, showed a median score of 46.59% of all family caregivers’ experienced burden in caring for their relative on haemodialysis. Health education and support for the family caregivers proved to be a need in improving and reducing the caregiver burden. Caregiver health is quickly becoming a public health care issue that requires a more focused attention from health professionals, policy makers and caregivers themselves to ensure the health and safety of those dedicating their lives to the care of their relatives on haemodialysis.
Keywords: Hemodialysis; Kidney Failure, Chronic--therapy